Agricultural-Food Sector Competitiveness of Eco Companies - Koneczna, Renata (Equilibrium. Equilibrium. Quarterly Journal of Economics and Economic Policy, 2011)
The aim of this paper is to present some methodological aspects connected with the evaluation of the growing market of goods facilitating protection of the natural environment in agricultural – food sector. The paper uses a measure which is used in the studies of foreign trade – RCA.